2022
DOI: 10.15406/mojfpt.2022.10.00266
|View full text |Cite
|
Sign up to set email alerts
|

Geopropolis: taxonomic dependence and compositional drawbacks

Abstract: The contents of total ashes and ethanol soluble substances were determined for propolis samples from species of two Meliponini genera: Melipona and Scaptotrigona. All Melipona samples corresponded to geopropolis (propolis containing aggregated soil material), with ash contents above 40%. Only one species of Scaptotrigona was shown to produce geopropolis, but with ash content (12%) much lower than Melipona samples. In Melipona a high negative correlation was observed between ash and ethanol solubles. Not only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Furthermore, some compounds such as sobrerol, oplopanone, α‐ionol and car‐3‐en‐5‐one were reported for the first time in propolis from the stingless bee of S. bipunctata . These data are consistent with the chemical profile of propolis from other brazilian stingless bees, for which it was shown that terpenoids and flavonoids are the two most commonly identified classes [36,37] …”
Section: Resultssupporting
confidence: 87%
“…Furthermore, some compounds such as sobrerol, oplopanone, α‐ionol and car‐3‐en‐5‐one were reported for the first time in propolis from the stingless bee of S. bipunctata . These data are consistent with the chemical profile of propolis from other brazilian stingless bees, for which it was shown that terpenoids and flavonoids are the two most commonly identified classes [36,37] …”
Section: Resultssupporting
confidence: 87%
“…2 Honey bees produce propolis by mixing resins they collect from several plant sources with their saliva and beeswax. 3,4 Biological properties of propolis components correspond mostly to substances derived from plant resins. Most types of propolis contain phenolic substances as major components, although terpenoids may be relevant propolis components, also derived from plant resins.…”
Section: Introductionmentioning
confidence: 99%